INTEGRATION BETWEEN TECHNICIANS AND REENGINEERING DECONSTRUCTED ANALYSIS TO RATIONALIZE COSTS AND SUPPORT COMPETITIVE ADVANTAGE - Mohammed Abed Kadhim; Ali Mohammed Thijeel AL-Mamouri (American Journals, 2023)
The intense competition witnessed by the contemporary industrial environment and the rapid developments have made economic entities practice their work in a competitive environment directed by the customer, and thus it is better for them to achieve added value on their part if they want to continue and maintain their competitive position. The research aimed to Explaining the integration between the techniques of re-engineering and deconstructed analysis to rationalize costs and support competitive advantage, as the use of deconstructed analysis and re-engineering techniques is directly linked to the desires and preferences of the customer and providing the product or service that suits his needs, and this would lead to improving the value of the product or service, As a result, rationalizing its costs, as well as using re-engineering technology before economic entities, leads to increasing the quality of the product, reducing its costs by making a radical change, and eliminating manufacturing process activities that do not increase the value of the product in relation to the customer’s requirements. Therefore, it is necessary to work on changing the reality of the cost system applied in the economic entity by modernizing it by applying modern technologies concerned with cost rationalization, represented by the deconstructed analysis technique for its prominent role in the process of calculating the cost of a solid scientific product, which was adopted in this research due to its focus on methods of manufacturing the cement product in light of the requirements. The customer has an employment relationship with the reengineering technology.
Keywords: process re-engineering, deconstructed analysis, cost rationalization, competitive advantage